Analisis Penerapan Pencatatan Laporan Keuangan Pada UMKM (Studi Kasus : Emir Roti) - Dharma, Budi; Hasibuan, Rukiana; Wiranti, Wiranti (Jurnal Manajemen Akuntansi (JUMSI), 2022)
Financial statements are a part of UMKM that must exist, because in order to develop a business by applying for credit or financing to creditors, namely the bank. Financial statements are very important because they are key in controlling business. However, in practice, because financial statements are not required in the law, many UMKM do not focus on preparing a good financial report. For UMKM, the profits generated can meet daily needs. Similarly, the UMKM Emir Roti who have difficulty in recording financial statements. However, Emir Roti keep records by preparing a special book to record the number of sales per day. However, the book cannot describe the financial condition of the Emir of Roti accurately. This study aims to determine the application of keunagan report recording that has been done by Emir Roti and for the sake of knowing the obstacles encountered when recording financial statements. This study uses descriptive qualitative approach. Primary data sources are interviews with UMKM owners and secondary data, namely documentation in the form of financial statements. The results showed that Emir Roti in recording its financial statements are not in accordance with SAK-ETAP because there are still obstacles faced by one of them at least knowledge of accounting. The researcher's suggestion is for the government to make more trainings on financial statements.